Differential Inhibition of Platelet Reactivity by Dual Therapy With Aspirin and Low-Dose Rivaroxaban in Peripheral Arterial Disease: A Pilot Study - Jurk, Kerstin; Rothenaicher, Korbinian F.; Groß, Kathrin; Rossmann, Heidi; Weißer, Gerhard; Schmidtmann, Irene; Münzel, Thomas; Espinola-Klein, Christine (Frontiers in Cardiovascular Medicine, 2022)
Patients with peripheral arterial disease (PAD) benefit from a combination therapy with acetylsalicylic acid (ASA, 100 mg once daily) plus low dose rivaroxaban (2.5 mg twice daily) compared to ASA monotherapy. In particular, major adverse cardiac and limb events were significantly reduced after peripheral endovascular revascularization (EVR). In this pilot study, the platelet activation status in vivo and platelet reactivity in vitro was longitudinally analyzed by flow cytometric assays and calibrated automated thrombography in platelet-rich plasma (PRP) from 10 patients with PAD receiving ASA (100 mg once daily) before EVR, ASA plus clopidogrel (75 mg once daily) after EVR and ASA plus rivaroxaban (2.5 mg twice daily) during long-term follow-up. Platelet responsiveness to clopidogrel was compared to additional 10 patients with stable PAD and clopidogrel (75 mg once daily) monotherapy. ASA plus rivaroxaban treatment resulted in a significantly decreased thrombin peak in PRP for two triggers, low concentration of tissue factor (TF) and thrombin, compared to ASA monotherapy. TF-controlled thrombin generation was additionally characterized by a significantly prolonged lag time in PRP and platelet-free plasma during ASA plus rivaroxaban combination therapy. In comparison, ASA plus clopidogrel treatment presented with a significant reduction of the thrombin peak in PRP, which was less pronounced than during subsequent ASA plus rivaroxaban therapy. Platelet responsiveness to clopidogrel was observed for 60% of patients receiving ASA plus clopidogrel and clopidogrel monotherapy, respectively. Blocking of CD36 on the platelet surface further reduced the thrombin peak in PRP induced by TF for all three therapy regimes. Platelet activation in vivo and in response to the GPVI-agonist convulxin or thrombin in vitro was similar, whereas integrin αIIbβ3 activation and α-granule release induced by the PAR-1 activating peptide TRAP-6 were significantly diminished during ASA plus rivaroxaban treatment compared to ASA monotherapy. In conclusion, the data of this pilot study indicate an inhibitory effect of rivaroxaban on the thrombin propagation phase of CD36-sensitive platelet thrombin formation in patients with PAD treated with ASA plus rivaroxaban combination therapy, which is associated with decreased PAR-1 but not thrombin-mediated platelet activation.